PHYTOCHEMICAL AND ANTIOXIDANT ACTIVITY OF CAMELLIA MISTLETOE (KORTHALSELLA JAPONICA) EXTRACTS - Kim, Min Young (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: This study was aimed to analyze the methanol or ethanol extract of Camellia mistletoe (Korthalsella japonica) growing in Jeju Island, Korea, for their composition of phenolics, flavonoids, and their antioxidant activity. Methods: Total flavonoid, total carotenoid and L-ascorbic acid contents were determined by using colorimetric assays, and the antioxidant attributes of the methanol and Camellia mistletoe extracts were assayed using in vitro models, including the following: Free radical (1,1-diphenyl-2-picrylhydrazyl, O2-• and NO•)scavenging, reducing power, and chelating ferrous ions. Results: Total flavonoid, total carotenoid and L-ascorbic acid contents were 20.3 and 14.9 mg RE/100 g, 4.4 and 1.7 mg/100 g, and 0.4 and 1.4 mg AA/100 g in the methanol and ethanol extracts of Camellia mistletoe, respectively. Based on IC50 values, both extracts were also found to possess potent antioxidant activities. Conclusions: Camellia mistletoe extracts could be the good antioxidant source and holds promise as a natural ingredient in functional food and pharmaceutical supplement.